Jóvenes universitarios en Lima: Política, medios y participación - Cano Correa, Ana María (2017)
In Peru, young college students have leading roles in social protest mobilizations even when they seldom belong to political organizations. This study aims to analyze the perception of current politics and its institutions among young college students, and to inquire into their interest on relevant events at their surroundings and into the importance gained by the media and the social networks concerning their information. The purpose of this project is also to examine the role assigned by college students to the university as a space of personal development and reflection. This project was carried out in Lima, Peru, directed to youngsters aged 17 to 25 from public and private universities. Opinions have been collected through six focus-groups and a survey applied to more than 400 students. The analysis concludes that college students distrust profoundly political parties and formal political organizations; likewise it shows they have a broad access to information sources, so as their willingness to solve Peru’s problematic issues. It also uncovers clear differences between students of private and public universities regarding attitudes for participating in political action, inside and outside the campus. From the study stems a proposal to provide young students at their campuses with opportunities to debate public issues of national and global interest as a part of their overall academic training.